Fostering Conservation via an Integrated Use of Conventional Approaches and High-Throughput SPET Genotyping: A Case Study Using the Endangered Canarian Endemics Solanum lidii and S. vespertilio (Solanaceae) - Gramazio, Pietro; Jaén-Molina, Ruth; Vilanova, Santiago; Prohens, Jaime; Marrero, Águedo; Caujapé-Castells, Juli; Anderson, Gregory J. (Frontiers in Plant Science, 2020)
Islands provide unique opportunities to integrated research approaches to study evolution and conservation because boundaries are circumscribed, geological ages are often precise, and many taxa are greatly imperilled. We combined morphological and hybridization studies with high-throughput genotyping platforms to streamline relationships and phylogenies in the endangered monophyletic and highly diverse lineage of Solanum in the Canarian archipelago. Inter-taxa hybridizations were performed, and morphological expression was assessed with a common-garden approach. Using the eggplant Single Primer Enrichment Technology (SPET) platform with 5,093 probes, 74 individuals of three endemic taxa (Solanum lidii, S. vespertilio subsp. vespertilio, and S. vespertilio subsp. doramae) were sampled for SNPs. While morphological and breeding studies showed clear distinctions and some continuous variation, inter-taxon hybrids were fertile and heterotic for vigour traits. SPET genotyping revealed 6,504 high-quality SNPs and supported four, not three, distinct taxonomic entities associated with post-emergence geological, ecological and geographic factors of the islands. Given the lack of barriers to hybridization among all the taxa and their molecular differences, great care must be taken in population management. Conservation strategies must take account of the sexual and breeding systems and genotypic distribution among populations to successfully conserve and restore threatened/endangered island taxa, as exemplified by Solanum on the Canary Islands.